Effect of Replacing Maize with Brewer’s Dried Grain in Broiler Finisher Diet - Ironkwe, M.O.; Bamgbose, A.M. (International Journal of Poultry Science, 2011)
The experiment was carried out using two hundred 4 weeks old broiler finisher birds to evaluate their response to diet with different levels of Brewers Dried Grain (BGD). The diet was made to replace maize with brewer’s dried grain at 0%, 25%, 50%, 75% and 100% to form treatment diets, 1, 2, 3, 4 and 5 respectively. The formulated rations were made in such a way that other ingredients apart from maize and brewer’s dried grain remained the same. The two hundred 4 weeks old broiler birds of Anak ® strains were allotted in a completely randomized Design into five treatment groups. Each treatment had 40 birds, which was replicated two times with 20 birds each. The experiment lasted for eight weeks with feed and water provided ad-libitum. Results showed significant differences in the birds growth performance, birds in T3 had the most superior (p